2017
DOI: 10.1098/rsob.160312
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and characterization of non-apical progenitors in the zebrafish embryo central nervous system

Abstract: Studies of non-apical progenitors (NAPs) have been largely limited to the developing mammalian cortex. They are postulated to generate the increase in neuron numbers that underlie mammalian brain expansion. Recently, NAPs have also been reported in the retina and central nervous system of non-mammalian species; in the latter, however, they remain poorly characterized. Here, we characterize NAP location along the zebrafish central nervous system during embryonic development, and determine their cellular and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…These observations show spinal neurons and NAPs share common stereotypical morphological behaviours, and further confirm that spinal Vsx1 NAPs and differentiating neurons share cellular and molecular characteristics as suggested previously (McIntosh et al, 2017).…”
Section: Non-apical Progenitors In Spinal Cord Also Extend Basal Protsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations show spinal neurons and NAPs share common stereotypical morphological behaviours, and further confirm that spinal Vsx1 NAPs and differentiating neurons share cellular and molecular characteristics as suggested previously (McIntosh et al, 2017).…”
Section: Non-apical Progenitors In Spinal Cord Also Extend Basal Protsupporting
confidence: 90%
“…In addition to the apical progenitors that generate most of the neurons of zebrafish CNS, a scarce population of basal progenitors that divide in non-apical locations is also present (Alexandre et al, 2010, McIntosh et al, 2017. We call these progenitors, Non-Apical Progenitors (or NAPs) and previously demonstrated that the majority of spinal NAPs express Vsx1 and share molecular and regulatory mechanisms with neurons (McIntosh et al, 2017). This prompted us to investigate whether spinal NAPs might also share the morphological programme of differentiation with neurons.…”
Section: Non-apical Progenitors In Spinal Cord Also Extend Basal Protmentioning
confidence: 99%
“…4H; Table S2.3), defining this domain as V2 interneurons. vsx1expressing cells in the hindbrain and spinal cord have been defined as non-apical progenitors, able to generate one excitatory (V2a) and one inhibitory (V2b) interneuron, and have been proposed to be a pool important for rapid generation of the sensory-locomotor circuit (McIntosh et al, 2017); their molecular signature is reported in Fig. 4D.…”
Section: Characterisation Of Neuronal Complexitymentioning
confidence: 99%
“…Fig.4). vsx1-expressing cells in the hindbrain and spinal cord have been defined as non-apical progenitors, able to generate one excitatory (V2a) and one inhibitory (V2b) interneuron, and proposed to be a pool important for rapid generation of the sensory-locomotor circuit (McIntosh et al, 2017); their molecular signature is reported in Fig.4D. Motor neurons can be identified in C8 (isl1, isl2, phox2a), and in the hindbrain lhx4, nkx6.1 and tbx3a are expressed in these cells (Fig.4D).…”
Section: Resultsmentioning
confidence: 99%